Development of an Impairment-Based Individualized Treatment Workflow Using an iPad-Based Software Platform - Kiran, Swathi; Roches, Carrie Des; Balachandran, Isabel; Ascenso, Elsa (Seminars in Speech and Language, 2014)
Individuals with language and cognitive deficits following brain damage likely require long-term rehabilitation. Consequently, it is a huge practical problem to provide the continued communication therapy that these individuals require. The present project describes the development of an impairment-based individualized treatment workflow using a software platform called Constant Therapy. This article is organized into two sections. We will first describe the general methods of the treatment workflow for patients involved in this study. There are four steps in this process: (1) the patient's impairment is assessed using standardized tests, (2) the patient is assigned a specific and individualized treatment plan, (3) the patient practices the therapy at home and at the clinic, and (4) the clinician and the patient can analyze the results of the patient's performance remotely and monitor and alter the treatment plan accordingly. The second section provides four case studies that provide a representative sample of participants progressing through their individualized treatment plan. The preliminary results of the patient treatment provide encouraging evidence for the feasibility of a rehabilitation program for individuals with brain damage based on the iPad (Apple Inc., Cupertino, CA).
Keywords: iPad; constant therapy; individualized; rehabilitation